Analisis Interaksi Cahaya Dan Material Dalam Teknologi Fotovoltaik - Waruwu, Meiman Herdiyanto; Zebua, Niko demus Baru (Jurnal Ilmu Ekonomi, Pendidikan dan Teknik, 2024)
Photovoltaic (PV) technology plays a key role in the transition towards renewable energy sources. The interaction of light with semiconductor materials is the main factor that determines energy conversion efficiency. This study analyzes the current literature on the interaction mechanisms of light with various types of photovoltaic materials, including silicon, perovskite, and organic materials. Research shows that optical properties, such as light absorption and scattering, have a significant effect on solar cell performance. In addition, factors such as crystal structure, morphology, and material doping also influence efficiency. These findings highlight the importance of innovation in material design and fabrication techniques to improve the efficiency of photovoltaic systems. Recommendations for further research are also discussed, especially in the development of new materials that can maximize light interactions.